2020
DOI: 10.24875/acme.m20000104
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility in the echocardiographic estimation of parameters of the right ventricle in prone position

Abstract: Background: Echocardiographic cardiac parameters in the prone position are usually obtained with an esophageal probe. The feasibility of obtaining them by means of a transthoracic approach is unknown. Objective: Estimating the feasibility to obtain parameters of the right ventricle by transthoracic echocardiography in prone position on the subject. Methods: Pilot design of consecutive case series without cardiopulmonary disease. Demographic, vital signs and echocardiographic variables were defined in the ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There are anecdotic reports of TTE 12 and a more extensive experience in transesophageal echocardiography during prone position ventilation, 13 but there is no standardization in the technique for image acquisition and measurements. Santos et al showed an adequate correlation of the RV measurements in prone compared with the supine position in 50 individuals; however, in this study, the evaluation was in healthy patients, not mechanically ventilated, 14 and the performance of critical care echocardiography in patients under IMV has unique challenges because the positive pressure caused by the pulmonary insuflation limits the acoustic window.…”
Section: Discussionmentioning
confidence: 72%
“…There are anecdotic reports of TTE 12 and a more extensive experience in transesophageal echocardiography during prone position ventilation, 13 but there is no standardization in the technique for image acquisition and measurements. Santos et al showed an adequate correlation of the RV measurements in prone compared with the supine position in 50 individuals; however, in this study, the evaluation was in healthy patients, not mechanically ventilated, 14 and the performance of critical care echocardiography in patients under IMV has unique challenges because the positive pressure caused by the pulmonary insuflation limits the acoustic window.…”
Section: Discussionmentioning
confidence: 72%
“…Noteworthily, Santos et al [ 16 ] focused their approach on RV function analysis in a group of spontaneous breathing healthy patients. They concluded that TTE in prone position is a useful tool to evaluate RV function; specifically, they observed that TAPSE and S’TDI were the parameters with the most superimposable results between supine and prone position.…”
Section: Literature Reviewmentioning
confidence: 99%